Perancangan User Experience Aplikasi berbasis Mobile pada Rindang menggunakan Proses Design Thinking - Muhammad Ihsan Fadhilah; Ismiarta Aknuranda; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Rindang is a marketplace service business of buying and selling plants, landscaping architectural services and also selling gardening tools in Indonesia. Rindang wanted to have a mobile application platform to help buying and selling plants easily, flexibly and efficiently. Based on these problems, the researcher provides a solution by designing the User Experience of the Rindang mobile application platform which creates the final result in the form of a high-fidelity prototype. The result will be able to make it easier for consumers to purchase plants in daily use. The design process uses the design thinking, in which there are five stages, namely empathize, define, ideate, prototype, and testing. Testing in this study will assess the aspects of learning ability, efficiency, and satisfaction by using usability testing with task scenarios and system usability scale (SUS). Based on the results of the test for the consumer system, it was obtained a value of â€œ82.5â€ which was included in the criteria of acceptability for the â€œhigh level of acceptanceâ€, the grade scale was â€œBâ€, and the adjective rating was classified as â€œalmost goodâ€. For a plant-selling system, it was obtained a value of â€œ85â€ which was included in the criteria of acceptability for the â€œhigh level of acceptanceâ€, the grade scale was â€œBâ€, and the adjective rating is â€œvery goodâ€. Whereas in the gardening service system, it was obtained a value of â€œ80â€ which was included in the criteria of acceptability for the â€œhigh level of acceptanceâ€, the grade scale was â€œCâ€, and the adjective rating is classified as â€œalmost goodâ€.